Visual signaling and reproductive biology in a nocturnal treefrog, genus Hyla (Anura: Hylidae) - Hartmann, Marília T. [UNESP]; Hartmann, Paulo A. [UNESP]; Haddad, Célio F.B. [UNESP] (De Gruyter, 2004)
We investigated reproductive activity, courtship behavior, call structure, body size, clutch size, oviposition site, and reproductive mode of Hyla sp. (aff. ehrhardti). Males called in all months, but showed a peak of activity during the rainy season. Three pair formations were observed and courtship involved stereotyped behavioral sequences, including visual signaling. Males emitted three different vocalization types: advertisement calls, courtship calls, and a vocalization of unknown function. Females attained larger body sizes than males and deposited an average of 74.5 unpigmented eggs per clutch. Early larval stages are aquatic but restricted to water in constructed subterranean nests; subsequent to flooding of nests, exotrophic tadpoles live in ponds or streams. Courtship behavior in Hyla sp. (aff. ehrhardti) is complex and the diverse repertoire of limb movements, exhibited by males, probably provide visual stimuli to females in this nocturnal treefrog. Hyla sp. (aff. ehrhardti) belongs to the H. albomarginata group. Considering the reproductive modes in this group, the complexes of H. albosignata and of H. albofrenata can be considered more close related to each other than to the H. albomarginata complex. © Koninklijke Brill NV, Leiden, 2004.
Keywords: courtship; frog; reproductive biology; visual cue; vocalization; Anura; Hyla; Hylidae